EFFECT OF COMPANY SIZE, FINANCIAL MISTAKES AND CHANGE MANAGEMENT REGARDING AUDITOR SWITCHING - Puji Lestari, Utami; Aniqotunnafiah, Aniqotunnafiah; Aeni, Nur (Journal of Accounting and Finance, 2024)
research objectives of this study are, to analyze the influence of company size on auditor switching in food and beverage sub-sector manufacturing companies in 2017-2021. To analyze the influence of Financial Distress on Auditor Switching in Food and Beverage Sub-Sector Manufacturing Companies in 2017-2021. To analyze the effect of Management Changes on Auditor Switching in Food and Beverage Sub-Sector Manufacturing Companies in 2017-2021. The type of research used is quantitative and type research data Which used in study This is data secondary. Population Which used in study This is company manufacturers listed on the Indonesian Stock Exchange (BEI). Sample selection carried out using a purposive sampling method. Data analysis method using analysis statictics descriptive and analysis regression logistics. This research using 110 samples data company. results following, Company size has no effect on auditor switching food and beverage sub-sector manufacturing companies. Financial distress positive and significant effect on auditors switching in food and beverage sub-sector manufacturing companies. Substitution management No influential to auditors switching on food and beverage sub-sector manufacturing companies.Â Keywords :Â  Switcing Auditor, Company Size, Financial Distress, Change of Management